2021
DOI: 10.1002/adfm.202104488
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Glucose Trigger‐Insulin Release System Based on Hydrogel Loading Bidentate β‐Cyclodextrin

Abstract: Initiated by the specific binding between D-glucose and biological receptors, the human body has a delicate metabolic system to regulate blood D-glucose levels, but failing to release insulin would induce hyperglycemia or type I diabetes. While insulin delivery is an effective form of hyperglycemia therapy, the self-regulated triggering of insulin release for on-demand supplementation remains inadequate. Here, a biomimetic glucose trigger-insulin release system, that is, a bidentate β-cyclodextrin-based hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…developed a biomimetic glucose trigger‐insulin release hydrogel system based on a bidentate‐ β ‐cyclodextrin preloaded with insulin. [ 215 ] The dual self‐regulated hydrogel showed specific binding between d ‐glucose and bidentate‐ β ‐cyclodextrin and exhibited macroscopic swelling due to proton release. While hydrogel expansion triggered release of preloaded insulin, isomers of d ‐glucose caused shrinkage and therefore delayed the release of insulin, enabling steady and prolonged blood glucose control (12+ h).…”
Section: Treating Diseases Resulting From Chronic Exposure To Environ...mentioning
confidence: 99%
“…developed a biomimetic glucose trigger‐insulin release hydrogel system based on a bidentate‐ β ‐cyclodextrin preloaded with insulin. [ 215 ] The dual self‐regulated hydrogel showed specific binding between d ‐glucose and bidentate‐ β ‐cyclodextrin and exhibited macroscopic swelling due to proton release. While hydrogel expansion triggered release of preloaded insulin, isomers of d ‐glucose caused shrinkage and therefore delayed the release of insulin, enabling steady and prolonged blood glucose control (12+ h).…”
Section: Treating Diseases Resulting From Chronic Exposure To Environ...mentioning
confidence: 99%
“…On the other hand, a smart stimulus, such as specific biomolecules overexpression, is also used to trigger drug release. For example, this can be seen in studies such as those reported by Wang et al [8] and Xu et al, in which modified βCD-loading insulin triggered release in the presence of high glucose concentrations [166,167]. In both studies, the formulations were demonstrated to be safe and specific glucose-responsive drug carriers with potential use for the therapy of diabetes.…”
Section: Cyclodextrin Derivates For Stimuli-controlled Drug Releasementioning
confidence: 87%
“…[ 169,198 ] A bidentate β ‐CD‐based hydrogel was preloaded with insulin to produce a dual d ‐glucose‐sensitive self‐regulated system. [ 199 ] The excellent potential to accurately monitor glucose levels and trigger insulin release was made possible by associating the CD with phenylboronic acid since CDs themselves or their direct derivatives are not selective toward d ‐glucose. An alternative glucose biosensor was also recently reported, based on β ‐CDs grafted onto magnetite/polydopamine with adsorbed glucose oxidase from Aspergillus niger .…”
Section: Cyclodextrinsmentioning
confidence: 99%